Determinant of human capital disclosure in the post IFRS regime: An examination of listed firms in Nigeria - Anifowose, Mutalib; Ab. Rashid, Hafiz Majdi; Annuar, Hairul Azlan (Accounting Research Institute (ARI), 2017)
This paper examines the possible determinants of human capital disclosure among listed firms in Nigeria. This paper reports the results from a longitudinal panel data based on 442 observations of firms listed on the main board of Nigeria Stock Market for the period 2012–2014. The paper contributes to the literature by extending previous determinants of intangible asset disclosure studies by considering the Nigerian economic and business environment due to recent adoption of international financial reporting standards. Based on agency and proprietary cost theories, the study employed seven possible determinants of voluntary disclosure and developed a checklist for human capital based on prior studies. The results of longitudinal data analyses indicate a significant positive influence on firm’s age, size and industry classification on human capital disclosure whereas the auditor type, profitability, inherent risk and joint audit have a significant negative influence on the of disclosure. The findings have practical implication for financial reporting council of Nigeria in developing HC disclosure standards and investors might utilise the findings in investment decision making process.